Mind the Gap: Molecular Architecture of the Axon Initial Segment – From Fold Prediction to a Mechanistic Model of Function?. Issue 20 (1st October 2021) - Quistgaard, Esben M.; Nissen, Josephine Dannersø; Hansen, Sean; Nissen, Poul
Graphical abstract: Highlights: The axon initial segment (AIS) showcases higher-order molecular function in neurons. AIS orchestrates the concerted output of voltage-gated ion channels forming action potentials. Spatial/dynamic distribution in 190 nm repeats is organized by microtubules, ankyrin G, α2- and β4-spectrins. Fold predictions can guide interpretation of experimental data on spatial distribution patterns of AIS. Fold predictions cannot resolve dynamic interaction networks of higher-order structures. Abstract: The axon initial segment (AIS) is a distinct neuronal domain, which is responsible for initiating action potentials, and therefore of key importance to neuronal signaling. To determine how it functions, it is necessary to establish which proteins reside there, how they are organized, and what the dynamic features are. Great strides have been made in recent years, and it is now clear that several AIS cytoskeletal and membrane proteins interact to form a higher-order periodic structure. Here we briefly describe AIS function, protein composition and molecular architecture, and discuss perspectives for future structural characterization, and if structure predictions will be able to model complex higher-order assemblies.